From trade wars to political agreement: History of the EEC-Japan conflictive dialogue (1970–1991) - M. P. Chizhevskaya (Японские исследования, 2024)
The article is devoted to the relations between Japan and the European Economic Community (EEC) in the period of the 1970s–1980s. It explains how these relations shifted from fixation on trade issues to signing the Hague Declaration of 1991 – the first bilateral political agreement; why institutionalization of the relations between these two economic powers and, at the same time, US partners did not happen earlier. The author chose not to use traditional descriptive research method based on chronological ordering in favor of a logical method based on discovery of objective and subjective factors influencing EU-Japan relations. The Introduction includes research relevance, peculiarities of the relations between Japan and the European Economic Community as a supranational organization, and the chronological framework explanation. The main part of the article is divided into four parts. The first one focuses on the basic characteristics of the period, the reasons for trade frictions, their most notable examples being singled out. The second part is devoted to the classification of the methods which the European side used to settle disputes. Their measures are classified in two categories: the measures aimed at the limitation of the Japanese import and at the stimulation of the EEC export. The third part traces the reasons why both sides expressed little interest in establishing political partnership, as well as traces the first steps aimed at its promotion. The final part focuses on the Hague declaration and the reasons which made its signing possible. The Conclusion contains the main results of the research. The author proposes that the objective factors for slow development of the political dialogue were the absence of common political agenda, which can be explained by geographical remoteness of the actors; orientation of both actors at the US in the security sphere, which eliminated the need to establish new partnerships. Among the subjective factors are the European elites’ fixation on trade frictions, which harmed the expansion of the negotiations agenda, and the Japanese elites’ uncertainty about the EEC’s identity as a fully legitimate European actor. This uncertainty was gradually eliminated with successful expansion of the bloc and its political integration. The signing of the Hague declaration became a reality when both sides saw the necessity of creating a political institutional framework for the settlement of trade frictions on a regular and constructive basis.